Enhancing Indonesian Vocabulary Learning through Index Card Match Media: Insights from a Lower Elementary Classroom Case Study - Anisa Fitri; Farid Rizqi Maulana; Deni Wardana; Yadi Suryadi; Mochammad Devi Cahya Ruhimat (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2026)
This study investigates the effectiveness of Index Card Match (ICM) media in enhancing Indonesian vocabulary achievement by lower elementary school students. An exploratory qualitative case study design was employed. Data were collected through triangulation, including analysis of instructional documents, classroom observations, and in-depth semi-structured interviews with 24 purposively selected participants. The data were analyzed using a thematic analysis supported by NVivo version 14. The findings shows that the implementation of ICM across three instructional stages generated several significant outcomes, including improved vocabulary comprehension, identification of conceptual errors and corresponding follow-up actions, comparative analysis of group performance, students’ cognitive development, and the creation of meaningful and enjoyable learning experiences. Although initial unfamiliarity with the media was observed, it gradually gave rise to students’ curiosity and enthusiasm, fostering active and collaborative classroom interactions and highlighting the teacher’s role in effective classroom management. This study offers a more comprehensive theoretical contribution than previous research by holistically capturing all stages of ICM utilization, rather than focusing solely on partial or quantitative learning outcomes. We support the adaptability of ICM for vocabulary development across diverse basic education contexts worldwide. Further research employing a quasi-experimental design is recommended to empirically test and strengthen these findings.